Association of Salivary Content Alteration and Early Ageusia Symptoms in COVID-19 Infections: A Systematic Review - Abduljabbar, Tariq; Alhamdan, Rana S.; Al Deeb, Modhi; AlAali, Khulud A.; Vohra, Fahim (European Journal of Dentistry, 2020)
Coronavirus disease 2019 (COVID 19) is a major threat to the health and prosperity of human life at present. It has resulted in loss of thousands of lives globally and has brought countries to the brink of economic, social, and health collapse. A major issue of this infection is the ease with which it transmits through salivary droplets and its survival for long durations outside the body. Therefore, its early detection is critical in prevention, diagnostic, and management efforts of COVID-19 patients. Loss of taste and smell is one of the early symptoms reported in these patients and the virus is abundantly found in the salivary secretion of the infected symptomatic and asymptomatic patients. Infection and inflammation of salivary glands are common among viral infections, particularly in the early stages, which lead to salivary composition changes. Chemosensory sensation of taste is critically dependent on the salivary flow rate and its inorganic constituents, protein levels, specific 3′,5′-cyclic adenosine monophosphate and 3′,5′-cyclic guanosine monophosphate levels, ghrelins, pH levels, and enzymes. Therefore, the question arises, “Does COVID-19 infection alter the salivary components and composition leading to early transient symptoms of Ageusia and hypogeusia?” This review shows association of the COVID-19 and Ageusia, in addition to the early viral infection of salivary glands and possible changes in salivary flow and content. Therefore, suggesting a potential association between early ageusia in COVID-19 infection and salivary compositional changes.
Keywords: SARS-COV-2; COVID-19; coronavirus; saliva; ageusia; salivary gland; viral infection